Uma leitura geográfica da reforma agrária potiguar - Costa, Maria José (2006)
It understands a study made concerning the main aspects of the Agrarian Reform and the Agricultural Nestings of the Rio Grande do Norte. For in such a way an inquiry became necessary initially on the origin of the Brazilian agrarian concentration passing for the donation of Sesmarias, Land Law, Statute of Land and Ith National Plan of the Agrarian Reformation, as well as of the Social Movements of fight for the land appeared since century XIX: Canudos, Contestado, Cangaço, Ligas Camponesas and MST. Drawing the fight for the land in the Rio Grande do Norte, we rescue the component elements of the first indications of the Agrarian Reform and formation of Agricultural Nestings in the State. In the attempt to unmask the current situation of the Settlements, we investigate some concerning aspects to the conditions of life of the seated ones, that it is marked by innumerable problems that go since the lack of water until the a precariousness of the infrastructure and presence of services, over all with relation to the education and health. For in such a way we work initially on the basis of diverse bibliographical readings, together data-collecting the official agencies and some directly involved entities with the Agrarian Reform in the RN. We utilized also the research of field in 27 Settlements of different Microregions of the State that consisted of the application of interviews together to the leaderships of these Settlements and application of forms with the seated families who resulted in a bigger knowledge concerning the reality of these areas that integrate the Politics of the Agrarian Reform